The role of prolactin/vasoinhibins in cardiovascular diseases - Hui Zhao; Sugang Gong; Yongcong Shi; Cijun Luo; Hongling Qiu; Jing He; Yuanyuan Sun; Yuxia Huang; Shang Wang; Yuqing Miao; Wenhui Wu (Animal Models and Experimental Medicine, 2023)
Abstract Prolactin (PRL) is a polypeptide hormone that is mainly synthesized and secreted by the lactotroph cells of the pituitary. There are two main isoforms of PRL: 23‐kDa PRL (named full‐length PRL) and vasoinhibins (including 5.6–18 kDa fragments). Both act as circulating hormones and cytokines to stimulate or inhibit vascular formation at different stages and neovascularization, including endothelial cell proliferation and migration, protease production, and apoptosis. However, their effects on vascular function and cardiovascular diseases are different or even contrary. In addition to the structure, secretion regulation, and signal transduction of PRL/vasoinhibins, this review focuses on the pathological mechanism and clinical significance of PRL/vasoinhibins in cardiovascular diseases.